The structural basis of β2 integrin intra-cellular multi-protein complexes - Bhattacharjya, Surajit (2022)
In multicellular organisms, cell adhesion is a pivotal physiological process which is essential for cell-cell communications, cell migration, and interactions with extracellular matrix. Integrins, a family of large hetero-dimeric type I membrane proteins, are known for driving cell adhesion functions. Among 24 different integrins, four β2 integrins, αL β2, αM β2, αX β2 and αD β2, are specific for cell adhesion and migration of leukocytes. Many cytosolic proteins interact with short cytosolic tails (CTs) of β2 and other integrins which are essential in bi-directional signaling processes. Further, phosphorylation of CTs of integrins regulates binding of intra-cellular proteins and signaling systems. In this review, recent advances in structures and interactions of multi-protein complexes of integrin tails, with a focus on β2 integrin, and cytosolic proteins are discussed along with a proposed future direction.